(untitled) (Jurnal Teknologi (Sciences & Engineering), 2022)
In this article, a nonlinear dynamical investigation of porose functionally graded cylindrical panels using a proposed analytical model is carried out. The material's properties are considered to be porosity-dependent and graded in the thickness direction, corresponding to a power-law distribution. The classical shell theory, with the geometrical shape of nonlinear in von Karman–Donnell, is employed to get the Lagrange motion equations. By applying the Galerkin procedure, the system of nonlinear dynamic vibration equations is found. The natural frequencies and dynamic amplitude vibrations are obtained by using the fourth-order Runge–Kutta approach. In numerical analyses, the effects of porosity factor, power-law index, porous FGM thickness, frequency–amplitude relation, and excitation force on the dynamic response of thin functionally graded porous cylindrical panels are investigated. Through the obtained results, it is discovered that the porosity coefficients have important effects on the natural frequencies and amplitude of the nonlinear dynamic response of the FG structures. It leads to a reduction in natural frequencies by 5.74 % at 10% pores.